Analysis of Input Impedance of the Traction Vehicle with DC Chopper as a Function of Operation Mode - Szeląg, Adam; Steczek, Marcin (Communications - Scientific letters of the University of Zilina, 2019)
A problem of analysis of the input impedance of a converter traction vehicle is presented in the paper. The value of input impedance of a traction vehicle has significant influence of compatibility between track circuits and traction vehicles. The model of chopper controlled DC series motor vehicle was implemented as a simulation model including all significant parameters of the whole system: substation-catenary-input filter-chopper. Exemplary results of analysis of the specific locomotive EM10 are included. The results both of analytical and simulation approach for low frequency input impedance computations were compared.